Rural banking for rural development in Zimbabwe - Matunhu, Jephias; Mago, Stephen (Kamla-Raj, 2016)
Rural poverty and underdevelopment in Zimbabwe are a result of colonialism, which emphasized urban development at the expense of rural development. The new political dispensation in the country has shifted towards improving the lives of people who reside in the rural areas. Despite a positive policy shift by President Mugabe’s government, the lack of finance remains one of the fundamental issues in rural development. The study investigated the opportunities and challenges for establishing rural banks in the country. This desktop research collected data from literature on rural development and financial intermediation. The findings of the study are that opportunities and challenges for establishing rural banks in Zimbabwe are social, political and economic in nature. Despite the challenges, rural banking deserves support from civil society , government and non-governmental organizations.